Comparative analysis of bone marrow derived mesenchymal stromal cells, cardiac regional stem cells and human skin fibroblasts - С. В. Павлова; Д. С. Сергеевичев; Е. В. Чепелева; В. С. Козырева; А. А. Малахова; И. С. Захарова; Е. В. Григорьева; Е. А. Покушалов; С. М. Закиян (Патология кровообращения и кардиохирургия, 2016)
A characteristic marker of cardiac stem cells (CSC) is a tyrosine kinase receptor c-kit. The cells with the c-kit+ phenotype can be easily isolated and cultivated in vitro. However, only CSC of postnatal animal hearts have the true cardiomyogenic potential. Currently it is being proposed that there are two lineages of c-kit+ cell population in heart. C-kit+ cells capable to differentiate into cardiomyocytes derive from the primary heart field and disappear soon after birth, and иc-kit+ cells of proepicardial origin expressing mesenchymal markers are capable to differentiate into endothelial, mural and fibroblast direction. We have previously described c-kit+ cells isolated from fragments of right atrial appendage, and investigated their angiogenic potential in vitro. In this study, we compared the surface markers of MSCs-BM, CSC and human dermal fibroblasts by flow cytometry and RT-PCR analysis.